Challenges in Monte Carlo Simulations as Clinical and Research Tool in Particle Therapy: A Review - Muraro, S.; Battistoni, G.; Kraan, A.C. (Frontiers in Physics, 2020)
The use and interest in Monte Carlo techniques in the field of medical physics have been rapidly increasing in the past years. This is the case especially in particle therapy, where accurate simulations of different physics processes in complex patient geometries are crucial for a successful patient treatment and for many related research and development activities. Thanks to the detailed implementation of physics processes in any type of material, to the capability of tracking particles in 3D and to the possibility of including the most important radiobiological effects, MC simulations have become an essential calculation tool not only for dose calculations, but also for many other purposes, like the design and commissioning of novel clinical facilities, shielding and radiation protection, the commissioning of treatment planning systems, and prediction and interpretation of data for range monitoring strategies. Despite the need for highly accurate calculation tools and the general consensus that Monte Carlo simulations can provide the requested accuracy, we are still far from applying MC routinely in patient treatments. From the vast amount of literature written on the subject, we can conclude that there is still a number of obstacles to overcome. The goal of this review is to discuss some of the currently remaining challenges in applying MC simulation tools widely for patient treatments. Undoubtedly it is a work for which a multi-disciplinary approach is required. Here we try to identify some of the aspects where the community involved in applied nuclear physics, radiation biophysics and computing development can contribute to find solutions. We have selected four specific challenges: i) the development of models in MC to describe nuclear physics interactions, ii) modelling of radiobiological processes in MC simulations, iii) developments of fast MC codes, and iv) developments of MC based treatment planning tools. For each of them, we describe the underlying problems, present selected examples of proposed solutions, and try to give recommendations for future research.